Hate Speech Analysis in Documentary Film “Ice Cold: Murder, Coffee and Jessica Wongso” - Adib Kurnaiwan; Tiara Nanda Dewi; Febri Wijayanti (Cakra Communico: Journal of Communication Science, 2024)
Hate speeches is a form of discrimination that can have a negative impact on victims . With the increasingly rapid development of technology , the media and the internet are often used as tools to carry out hate speech , one of which is represented in films . Several previous studies have shown that hate speeches through the media can harm society and strengthen negative stereotypes against certain groups . Most of the hate speeches comes from the language used . This research aims to analyze the frequency level of forms of verbal hate speech in the documentary film "Ice Cold : Murder , Coffee and Jessica Wongso". This research uses a quantitative content analysis method with the population in this study consisting of all verbal communication including dialogue and narratives containing hate speech, which appeared in the documentary film "Ice Cold : Murder , Coffee and Jessica Wongso".